KELAYAKAN MEDIA PEMBELAJARAN MIKRO REFLEKTIF BERBASIS VIRTUAL REALITY TERINTEGRASI TPACK - Ginting, Fajrul Wahdi; Unaida, Ratna; Widya, Widya; Sakdiah, Halimatus (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
One form of microteaching learning innovation is designing micro-reflective learning media based on Virtual Reality (VR). This research constitutes developmental research designed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) aimed at developing VR-based learning media. Data were obtained from validation sheets and questionnaires processed using descriptive statistics to determine the feasibility and practicality of using VR-based learning media. The research results indicate that the assessment from subject matter experts shows a relevance rating of 92%, accuracy aspect 92%, presentation ease aspect 88%, presentation systematicity of 89%, and presentation suitability aspect of 95%. Similarly, the assessment by subject matter experts, with a percentage of 91.20, indicates a highly valid criterion. The development of VR media, evaluated from media validation, is stated to be highly valid with a percentage of 91.60%, based on several indicators: media object display, 3D graphics, object modifications, sound clarity, and media ease, each obtaining percentages of 92%, 92%, 89%, 97%, and 88%, respectively. The media trial results conducted on 25 students yielded a percentage of 90% categorized as highly suitable for use in microteaching learning processes